2x+4=3(x-2)=1

Simple and best practice solution for 2x+4=3(x-2)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+4=3(x-2)=1 equation:



2x+4=3(x-2)=1
We move all terms to the left:
2x+4-(3(x-2))=0
We calculate terms in parentheses: -(3(x-2)), so:
3(x-2)
We multiply parentheses
3x-6
Back to the equation:
-(3x-6)
We get rid of parentheses
2x-3x+6+4=0
We add all the numbers together, and all the variables
-1x+10=0
We move all terms containing x to the left, all other terms to the right
-x=-10
x=-10/-1
x=+10

See similar equations:

| 21=-7(2x-7 | | 4(n+3)=1n-2 | | (x+6)/7=-6 | | (x-3)/4=-6 | | 10y^2-34y+44=0 | | 3x-16+6×+7=180 | | 3(7-2a)=(126-5a) | | 3x-16+6×+2=180 | | y^2+4y+8=64 | | (x/5)-1=-7 | | 2.5(x)=60 | | -9/2x+4=-9/2 | | 2x+4(x+1)=12 | | (x/4)-5=-5 | | (x/7)-7=0 | | (x/3)+3=-6 | | (x/12)+3=8 | | 3x+70=7x+30 | | 9(y+5)+y=3(y+4)+4 | | 500x=50x+50000 | | C=2.5x+19500 | | 9(2x-5)-3(5-2x)=4(10-3x)+2(4x-1) | | 8x-20=53 | | (x)+(x)=42 | | 3x+14=x+10 | | 40-3v=2v | | 6a+7=26 | | 40-3v=2 | | 11x-47=6×-2 | | x(×-4)=x^2+3x+6 | | 87.41/x=4/100 | | 3m-7=-7-5m |

Equations solver categories